Ferrocene-Based Bioactive Bimetallic Thiourea Complexes: Synthesis and Spectroscopic Studies - Shafqat Ali; Ghulam Yasin; Zareen Zuhra; Zhanpeng Wu; Ian S. Butler; Amin Badshah; Imtiaz ud Din (Bioinorganic Chemistry and Applications)
Bioactive 1,1′-(4,4′-di-ferrocenyl)di-phenyl thiourea and various metal complexes of this ligand have been successfully synthesized and characterized by using physicoanalytical techniques such as FT-IR and multinuclear (1H and 13C) NMR spectroscopy along with melting point and elemental analyses. The interaction of the synthesized compounds with DNA has been investigated by using cyclic voltammetric and viscometric measurements. The intercalation of the complexes into the double helix structure of DNA is presumably occurring. Viscosity measurements of the complexes have shown that there is a change in length and this is regarded as the least ambiguous and the most critical test of the binding model in solution. The relative potential of the complexes as anti-bacterial, antifungal, and inhibition agents against the enzyme, alkaline phosphatase EC 3.1.3.1, has also been assessed and the complexes were found to be active inhibitors.